Combined Open-Slot and Monopole 8 × 8 High-Isolation Broadband MIMO Antenna System for Sub-6 GHz Terminals - Jie Guo; Shaoqing Zhang; Chong-Zhi Han; Liang Zhang (International Journal of Antennas and Propagation)
In this article, an 8 × 8 MIMO antenna system with multidecoupling structures is proposed for the fifth-generation (5G) terminal applications. First, an antenna element consisting of an L-shaped open slot with dimensions of 5.6 × 5 mm2 and two bent-L-shaped monopoles with dimensions of 12.7 × 6.1 mm2 is introduced. Due to coupling feed technology, the initial open slot owns a wide bandwidth from 3.62 GHz to 4.82 GHz. For broadening the bandwidth of the initial antenna element, two bent-L-shaped monopoles are added to the open slot to adjust the input impedance. By optimizing the parameters of monopoles, the proposed antenna element has been finally determined and the bandwidth of the antenna element has been broadened (2.82 GHz to 5.23 GHz). Second, a dual antenna pair is constructed by placing the two antenna elements with an edge-to-edge distance of 27 mm in a mirror image placement; the 8 × 8 MIMO antenna system is brought about by symmetrically disposing four such antenna pairs with an edge-to-edge distance of 47 mm. Moreover, the isolation of two closely placed antenna elements is achieved by the parasitic strip-loading technique and defective ground techniques. Due to the decoupling techniques used in the 8 × 8 MIMO antenna system, the average isolation has been optimized from 13.2 dB to 21.9 dB and the total efficiency of each antenna element has been improved from a worst 20% to over 45%. Besides, the calculated mean efficiency gain is less than 1 dB, and the calculated envelop correlation coefficient (ECC) is lower than 0.01 for desired frequency bands. Furthermore, the proposed 8 × 8 MIMO antenna system has the measured broadband bandwidth from 3.28 GHz to 5.05 GHz (covering N77, N78, and N79 bands) and a compatible dimension for ultra-thin mobile phones. The simulated results of this work are all obtained from EM software CST STUDIO SUITE 2019. In general, the proposed 8 × 8 MIMO antenna system with a high-isolation property provides a hopeful solution to 5G ultra-thin mobile phones.